Avrupa'daki tasnif sistemlerine dair gelişmelerin Türk arşivcilik tarihine etkisi: Arşivlerde usul ve kaide - YILMAZ ŞENTÜRK, ELİF (My University, 2022)
Aim:The 20th century is a period in which developments in document classification systems were experienced in Europe. Turkey kept abreast of these developments due to books and articles published on this topic. In this study, two separate articles named \"Procedure andPrinciples in Archives (Arşivlerde Usul ve Kaide), which were translated from Dutch to Ottoman Turkish and published in Istanbul Şehremaneti Mecmuası, were evaluated, and the aim was to reveal their effects on archiving in Turkey.Method:Document analysis was employed as a research method for this study, and document scanning methods were used to convert the above-mentioned articles from Ottoman Turkish to the modern Turkish Alphabet. A simple transcription method was used in this process.Findings:It was determined that the first of the articles originated from the book named \"Ordening in de Administratie\" written by Frits Donker Duyvis, the head of the second edition of Universal Decimal Classification. For the author of the second article, only the initials H.N. are used. Using archival documents, ithas been attempted to prove that the initials belong to the name Hayrettin Nedim Göçen. Inthe first article, subject classification systems are explained, and recommendations are given for the application of Universal Decimal Classification to archives. A survey of current literature confirms that the document management processes mentioned in both articles are still valid today.Conclusion:The 20th century was a period when subject classification systems came to the fore. It is demonstrated that the developments in the field of document management in Europe in this century have affected the library, filing, and archival practices in Turkey. Decimal and subject classification systems are still used today. Access to documents is a subject studied in every period, but the personnel who work in this field are the most crucial document management element.Originality:Unlike other studies in the literature, it is argued that the standard file plan used in Turkey emerged as a result of the developments in document management in Europe. Publications such as \"Procedure and Principles in Archives\" in the Archives, published in Istanbul Şehremaneti Mecmuası, Turkey\"sfirst municipal journal, greatly influenced the methods in Turkey through publicizing the standards emerging in Europe.

maç: 20. yüzyıl, Avrupa’da belge tasnif sistemlerine dair gelişmelerin yaşandığı bir dönemdir. Söz konusu gelişmeler yayınlanan kitap ve makaleler sayesinde Türkiye’de takip edilebilmiştir. Bu çalışmada Felemenkçe’den Türkçe’ye tercüme edilerek İstanbul Şehremaneti Mecmuası’nda eski harflerle yayınlanan ‘Arşivlerde Usul ve Kaide’ isimli iki ayrı makale değerlendirilmiş, Türkiye’de, arşivcilik alanındaki etkilerinin ortaya konulması amaçlanmıştır. Yöntem: Araştırma yöntemi olarak doküman analizi ve belge tarama yöntemleri kullanılan bu çalışma için söz konusu makaleler Osmanlı Türkçesi’nden Yeni Türk Alfabesi’ne tahvil edilmiştir. Bu işlem yapılırken basit transkripsyon yöntemi kullanılmıştır. Bulgular: Makalelerden ilkinin, Universal Decimal Classification’un ikinci edisyonunun başkanı Frits Donker Duyvis tarafından kaleme alınan ‘Ordening in de Administratie’ isimli kitaptan alındığı tespit edilmiştir. İkinci makalenin yazarı için yalnızca H.N. harfleri kullanılmıştır. Bu ismin Hayrettin Nedim Göçen olduğu arşiv belgeleriyle kanıtlanmaya çalışılmıştır. İlk makalede konu tasnif sistemleri anlatılmış, Universal Desimal Classification’un arşivlere uygulanmasına yönelik tavsiyeler verilmiştir. Makalelerde geçen belge yönetimi işlemlerinin günümüzde de geçerli olduğu güncel literatüre dayalı olarak sunulmuştur. Sonuç: 20. yüzyıl konu tasnif sistemlerinin ön plana çıktığı bir dönemdir. Bu yüzyılda Avrupa’da belge yönetimi alanındaki gelişmelerin Türkiye’deki kütüphane, dosyalama ve arşiv uygulamalarını etkilediği ortaya konulmuştur. Desimal ve konu tasnif sistemleri günümüzde de kullanılmaktadır. Belgeye erişim her dönem üzerinde çalışılan bir konudur ancak bu alanda çalışacak olan personel belge yönetiminin en önemli unsurudur. Özgünlük: Bu çalışmada, literatürdeki diğer çalışmalardan farklı olarak Türkiye’de kullanılan standart dosya planının, Avrupa’daki belge yönetimine dair gelişmelerin bir yansıması olarak ortaya çıktığı iddia edilmektedir. Türkiye’nin ilk belediyecilik dergisi olan İstanbul Şehremaneti Mecmuası’nda yayınlanan ‘Arşivlerde Usul ve Kaide’ gibi yayınlar Avrupa’da ortaya çıkan standartların bilinmesini sağlayarak Türkiye’deki yöntemleri de büyük ölçüde etkilemiştir.
He effects of the developments of the classification systems in europe on Turkish archival history: Procedure and the principle in the archives
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Evrensel Onlu Sınıflandırma; arşivcilik; düzenleme